2006
DOI: 10.1143/jjap.45.8430
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Multilayer SiOx(CH)yNz Film Deposited by Low Temperature Plasma Enhanced Chemical Vapor Deposition Using Hexamethyldisilazane/Ar/N2O

Abstract: We show the existence of a new class of astrophysical objects where the self-gravity of the dust is balanced by the force arising from shielded electric fields on the charged dust. The problem of equilibrium dust clouds is formulated in terms of an equation of hydrostatic force balance together with an equation of state. Because of the dust charge reduction at high dust density, the adiabatic index reduces from two to zero. This gives rise to a mass limit M AS for the maximum dust mass that can be supported ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…1. All the spectra showed strong absorbance bands at around 840, 1170, 2150, and 3350 cm − 1 originated from Si-N bonding [6], Si-O bonding [7], Si-H bonding, and the bonding from -OH and N-H [8], respectively. The Si-N absorbance peak at the wave number around 840 cm − 1 was shifted to the high wave number (to 904 cm − 1 ) with increasing the ratio R. It is reported that Si-N band is shifted depending on the relative concentration of Si-H (2100 -2200 cm − 1 ) and N-H (around 3350 cm − 1 ) in the deposited films [9].…”
Section: Resultsmentioning
confidence: 99%
“…1. All the spectra showed strong absorbance bands at around 840, 1170, 2150, and 3350 cm − 1 originated from Si-N bonding [6], Si-O bonding [7], Si-H bonding, and the bonding from -OH and N-H [8], respectively. The Si-N absorbance peak at the wave number around 840 cm − 1 was shifted to the high wave number (to 904 cm − 1 ) with increasing the ratio R. It is reported that Si-N band is shifted depending on the relative concentration of Si-H (2100 -2200 cm − 1 ) and N-H (around 3350 cm − 1 ) in the deposited films [9].…”
Section: Resultsmentioning
confidence: 99%
“…This low-temperature process involves the dissociation of volatile precursors with plasma and directing the reactive mixture onto the substrate surface. 6,7 However, PECVD requires an expensive vacuum system because it is operated at low pressures. This is particularly a problem when PECVD is used to deposit uniform films on an extremely large area substrate, such as flat-panel displays and flexible displays for the next generation, due to the difficulty in generating uniform plasma over a large area.…”
mentioning
confidence: 99%
“…This may be the case due to the fact that HMDSN molecules inherit lower intrinsic binding energies as compared with HMDSO molecules due to the significantly lower electronegativity of Nitrogen as compared with that of Oxygen. [ 14,16–18 ] HMDSN, therefore, needs less energy per molecule to decompose into fragments than HMDSO. The surplus energy may contribute to a higher degree of volume polymerization and, therefore, leads to deposition of larger fragments, which enable a faster coating.…”
Section: Resultsmentioning
confidence: 99%